Influence of Hotel Sustainable Management Practices on Customer Behaviour in Selected Hotels in Ilorin-West Lga, Kwara State Nigeria - P. N. Meduna; C. A. Jeje; F. O. Otelaja; P. O. Ovwie; E. A. Irunokhai; Z. James (Journal of Applied Sciences and Environmental Management, 2024)
The objective of this paper is to study the influence of hotel management practices on customer behaviour in selected hotels within Ilorin West Local Government Area of Kwara state. The hotels were selected using the observation and purposive sampling method while the random sampling technique was used to select the members of staff for each hotel. A total of 100 respondents were issued well-structured questionnaires. However 85 questionnaires were retrieved. Data was analysed using descriptive statistic. The findings revealed that the hotels engage in sustainable management practices which includes social practices, environmental practices and economic practices with the exception of higher remuneration for employees, aggressive marketing by employees, and waste recycling. The environmental and economic practices which are not adopted by the hotels could cause potential bad business for the hoteliers and its customers as well as its local communities because the poor environmental maintenance negatively affects human health. This is evident in the fact that there is no recycle of waste and most likely there might be open dumping of waste However, the sustainable management practices which are not carried out by the hotels have little or no effect on customer behaviour and as customers are more interested in repeat-buy and patronising the hotels more often.